WOMEN'S DIOCESAN SCHOOLS IN THE SYSTEM OF RELIGIOUS EDUCATION IN VOLYN (1864-1917) - Leliukh, Sofia (Mountain School of Ukrainian Carpaty, 2024)
Aim and tasks research is to describe the content, forms, and methods of teaching and spiritual upbringing of girls in the women's diocesan schools of Volyn in the 19th and early 20th centuries. The article analyzes the content and characteristics of the activities of women's religious educational institutions in Volyn – diocesan schools for daughters of the clergy, which were established in Zhytomyr (1864) and Kremenets (1884). The main features of the Volyn Diocesan School's operations during the three-class stage (1864-1884), the six-class stage (1884-1903), and the stage under the 1891 Statute (1903-1914) are defined. It is noted that the goal of women's religious educational institutions was focused on studying the Law of God, prayer practices, and developing household management skills. The content of education at the Volyn Diocesan Women's School is analyzed. Special attention is given to the role of pedagogy as a subject introduced into the curriculum of Volyn's diocesan schools for women at the end of the 19th century, which granted graduates the right to claim the title of home tutors. The importance of establishing a parish school at the Volyn Diocesan School as a practice site for future teachers is emphasized. The main forms and methods of educational activities in women's diocesan schools in Volyn, predominantly reproductive, are identified: reading, copying texts, memorizing them, and reproducing them from memory, as well as written creative assignments. A special place in the network of religious schools in Volyn during the studied period was occupied by women's diocesan schools for girls of clerical origin. Thus, not only boys but also girls born into the families of priests and other representatives of the clergy received religious education and remained within this spiritual estate in adulthood, ensuring the stratification of this social group over a long historical period. The article also examines the personnel of the women's religious educational institutions (headmistress, dean, governesses, teachers, assistant governesses, supervisor of household matters, etc.).